The Immunologic Role of Gut Microbiota in Patients with Chronic HBV Infection - Yang, Ruilin (J Immunol Res, 2018)
Hepatitis B can cause acute or chronic liver damage due to hepatitis B virus (HBV) infection. Cirrhosis or hepatocellular carcinoma (HCC) caused by chronic HBV infection often leads to increased mortality. However, the gut and liver have the same embryonic origin; therefore, a close relationship must exist in terms of anatomy and function, and the gut microbiota plays an important role in host metabolic and immune modulation. It is believed that structural changes in the gut microbiota, bacterial translocation, and the resulting immune injury may affect the occurrence and development of liver inflammation caused by chronic HBV infection based on the in-depth cognition of the concept of the “gut-liver axis” and the progress in intestinal microecology. This review aims to summarize and discuss the immunologic role of the gut microbiota in chronic HBV infection.